2012
DOI: 10.19030/iber.v11i7.7059
|View full text |Cite
|
Sign up to set email alerts
|

Share Valuation Methods And Data Source-Based Accounting In An Emerging Stock Market: The Case Of The Kuwaiti Stock Market

Abstract: This paper uses a questionnaire survey to investigate share valuation methods and the sources of information employed by Kuwaiti investors; it compares the appraisal techniques and the sources of information employed by Kuwaiti investors to those used in other developed and emerging stock markets. The findings suggest that Kuwaiti investors behave like their counterparts in other stock markets; fundamental analysis is the main appraisal technique used by investors; technical analysis and risk analysis are rank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…Furthermore, this study is comprehensive because it investigates Kuwait stock market participants' perceptions of a broad set of corporate information sources-general, financial, nonfinancial, social, corporate governance, and type of valuation methods-useful for investment decisions making. Furthermore, previous research in the field (e.g., Abu-Nassar & Rutherford, 1996;Al-Attar & Al-Khater, 2007;Al Sawalqa, 2012;Almujamed et al, 2012) has shown that different types of investors have used many sources of information; across these studies, no one source was found to be the best or most important source for investors. Therefore, it can be inferred that all the related corporate information sources are useful for investment decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, this study is comprehensive because it investigates Kuwait stock market participants' perceptions of a broad set of corporate information sources-general, financial, nonfinancial, social, corporate governance, and type of valuation methods-useful for investment decisions making. Furthermore, previous research in the field (e.g., Abu-Nassar & Rutherford, 1996;Al-Attar & Al-Khater, 2007;Al Sawalqa, 2012;Almujamed et al, 2012) has shown that different types of investors have used many sources of information; across these studies, no one source was found to be the best or most important source for investors. Therefore, it can be inferred that all the related corporate information sources are useful for investment decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This review of prior studies shows that only two studies (Almujamed et al, 2012;Naser et al, 2003) discussed financial information sources and investment decision-making in Kuwait. The current study is different from these two studies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations